Characteristic Problems in the Application of Modern Educational Technology in Teaching: the Possibility of Overcoming Them - Arsić, Zvezdan M.; Zaporožac, Ivan (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
As a consequence of rapid technical, scientific and technological development, there was a need for changes in education and teaching. These changes are manifested both in the organization of educational content and in the introduction and application of new procedures, methods and tools. However, despite the knowledge that the goals and principles of the concept of education at the current stage of social development imply a complete reconstruction of the traditional educational system and teaching and that the application of modern educational technology creates conditions for acquiring more dynamic, quality and complex knowledge, there are numerous problems. Recognizing the fact that the application of modern educational technology can significantly contribute to the achievement of educational goals, our intention is to work, in addition to terminological and conceptual definition of educational technology, to focus on the causes of problems in this domain and to point out possible ways to overcome them.